A self-assembled amphiphilic polysaccharide-based co-delivery system for egg white derived peptides and curcumin with oral bioavailability enhancement. Issue 21 (27th September 2021) - Yang, Meng; Liu, Jingbo; Li, Yajuan; Yang, Qi; Liu, Xuanting; Liu, Chunmei; Ma, Sitong; Liu, Boqun; Zhang, Ting; Xiao, Hang; Du, Zhiyang
Abstract : Schematic illustration of the amphiphilic nanoparticles with respect to co-encapsulation, interaction, and oral bioavailability enhancement (1 + 1 > 2) for egg white derived peptide (EWDP) and curcumin. Abstract : Egg white derived peptides (EWDP) and curcumin are well known for diverse biological activities, but the combinational usage of the two natural nutraceuticals is extremely limited by their low oral bioavailability and distinctly different polarities. Therefore, this study aimed to exploit a facile self-assembled amphiphilic system for oral co-delivery of hydrophilic egg white derived peptides (EWDP) and hydrophobic curcumin. The hydrophobic curcumin was first loaded into the hydrophobic cavity of β-cyclodextrin (β-CD) as a core. Then, the hydrophilic EWDP was absorbed into the region between the core and the N -[(2-hydroxy-3-trimethyl ammonium) propyl] chitosan (HTCC) shell to form the amphiphilic nanoparticles (NPs) via layer-by-layer self-assembly. The resulting NPs showed ideal oral applicability with excellent colloidal properties and encapsulation capacity for EWDP and curcumin at pH 2.0–7.0. X-ray Photoelectron Spectroscopy (XPS), Fourier transform infrared spectroscopy (FTIR), nuclear magnetic resonance ( 1 H NMR), X-ray diffraction (XRD) and differential scanning calorimetry (DSC) results indicated that hydrogen bonding and hydrophobic interaction were the main driving force for the formation of amphiphilic NPs. Upon combination with HTCC, EWDP (both shell material and core nutraceuticals) could facilitate curcumin loading into the deeper β-CD cavity site with admirable solubility improvement. Moreover, EWDP and curcumin after co-delivery exhibited superior bioavailability (especially for bioactivity and cellular absorption) than the simple mixture and conventional curcumin inclusion complex. Overall, these findings are enlightening for the rational peptide based oral co-delivery system formulations for a broader range of hydrophilic and hydrophobic nutraceuticals (initially synergistic or not) in the food and related health-promoting fields.